DEVELOPMENT OF MICROSITE-BASED LEARNING MEDIA (HUMA ITAH) FOR ENGLISH SUBJECT AT SMPN - Aditiya Dwi Nurrachmat; Chandra Anugrah Putra; Endang Sri Suyati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This research was motivated by the low engagement and learning outcomes of students in English learning due to the dominance of conventional teaching media and limited use of digital technology in the classroom. The study aimed to develop and evaluate a web-based microsite learning media called “Huma Itah” to improve students’ learning effectiveness, practicality, and engagement in English subjects at SMP Negeri 5 Muara Teweh. This research employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, expert validation, questionnaires, and pre-test and post-test instruments. The data were analyzed using qualitative and quantitative descriptive analysis. The results showed that the developed microsite achieved a very high level of practicality (96.08%) and was categorized as highly valid based on expert validation. In terms of effectiveness, the learning outcomes improved significantly, with the average score increasing from 9.14 to 15.61 and an N-Gain score of 0.60 (moderate to high category). The microsite also enhanced student motivation and engagement through interactive multimedia, visual content, instant feedback quizzes, and integration of local cultural context. The discussion indicates that the effectiveness of the media is supported by multimedia learning theory, cognitive load theory, and culturally responsive teaching principles. In conclusion, the “Huma Itah” microsite is an effective, practical, and innovative learning media that significantly improves students’ English learning outcomes and engagement in junior high school settings.. ABSTRAK Penelitian ini dimotivasi oleh rendahnya keterlibatan dan hasil belajar siswa dalam pembelajaran Bahasa Inggris karena dominasi media pengajaran konvensional dan terbatasnya penggunaan teknologi digital di kelas. Studi ini bertujuan untuk mengembangkan dan mengevaluasi media pembelajaran berbasis web microsite bernama “Huma Itah” untuk meningkatkan efektivitas, kepraktisan, dan keterlibatan belajar siswa dalam mata pelajaran Bahasa Inggris di SMP Negeri 5 Muara Teweh. Penelitian ini menggunakan pendekatan Penelitian dan Pengembangan (R&D) dengan model ADDIE, yang terdiri dari tahapan analisis, desain, pengembangan, implementasi, dan evaluasi. Data dikumpulkan melalui observasi, wawancara, validasi ahli, kuesioner, dan instrumen pre-test dan post-test. Data dianalisis menggunakan analisis deskriptif kualitatif dan kuantitatif. Hasil menunjukkan bahwa microsite yang dikembangkan mencapai tingkat kepraktisan yang sangat tinggi (96,08%) dan dikategorikan sebagai sangat valid berdasarkan validasi ahli. Dari segi efektivitas, hasil belajar meningkat secara signifikan, dengan nilai rata-rata meningkat dari 9,14 menjadi 15,61 dan skor N-Gain sebesar 0,60 (kategori sedang hingga tinggi). Mikrositus ini juga meningkatkan motivasi dan keterlibatan siswa melalui multimedia interaktif, konten visual, kuis umpan balik instan, dan integrasi konteks budaya lokal. Diskusi menunjukkan bahwa efektivitas media ini didukung oleh teori pembelajaran multimedia, teori beban kognitif, dan prinsip pengajaran yang responsif secara budaya. Kesimpulannya, mikrositus “Huma Itah” adalah media pembelajaran yang efektif, praktis, dan inovatif yang secara signifikan meningkatkan hasil belajar bahasa Inggris dan keterlibatan siswa di lingkungan sekolah menengah pertama.